Venous Thromboembolism Issues in Women - Linnemann, Birgit; Rott, Hannelore; Zotz, Rainer; Hart, Christina (Hämostaseologie, 2022)
The lifetime risk of venous thromboembolism (VTE) is slightly higher in women than in men. There are several issues related to VTE that are unique to women. Combined hormonal contraceptives and pregnancy increase the risk of VTE in women of childbearing age, whereas hormone replacement therapy increases the VTE risk of postmenopausal women. Hereditary thrombophilia and risk factors such as older age, obesity, or smoking contribute to the risk increase. In women diagnosed with acute hormone-related VTE who are treated with oral anticoagulants, adequate contraception is mandatory to avoid unwanted pregnancies. According to current knowledge, hormonal contraception may be continued during anticoagulant therapy but must be switched to an estrogen-free contraception method at least 6 weeks before the termination of anticoagulation. VTE is also a major cause of maternal morbidity and mortality during pregnancy and the postpartum period. Currently, assisted reproduction technologies such as in vitro fertilization are widely used to treat couples affected by infertility. Complications of fertility treatment comprise VTE cases, especially in women with ovarian hyperstimulation syndrome. With this review, we intended to focus on VTE issues in women and summarize current evidence and guideline recommendations.
Keywords: venous thromboembolism; contraception; hormone replacement therapy; thrombophilia; women